The Changing Village Environment In Southeast Asia : Applied anthropology and environmental reclamation in the northern Philippines. - Wallace, Ben (Taylor & Francis Ltd., 2005)
This book follows the work of the 'Good Roots Project' on Luzon in the Philippines.